Field implementation of a floating wetland system in Kranji reservoir - Lai, Yoke Yee (2011)
The floating wetland system (FWS) has been used for water treatment due to their low maintenance costs, ecological benefits and aesthetic nature. It is being encouraged in tropical countries to improve the quality of reservoir inflows. Furthermore, it is most suitable for water catchments since it is sustainable in areas of high water depths compared to constructed wetlands.